2017
DOI: 10.1155/2017/6212605
|View full text |Cite
|
Sign up to set email alerts
|

Skin Friction Reduction Characteristics of Nonsmooth Surfaces Inspired by the Shapes of Barchan Dunes

Abstract: A new type of nonsmooth surface inspired by the shape of barchan dunes has been proposed and is intended to reduce skin friction, a major cause of overall drag. Simulations were carried out to obtain skin friction reduction characteristics for the nonsmooth surface using the commercial computational fluid dynamics software Fluent. A realizable k-ε model was employed to assess the influence of the nonsmooth structure on turbulent flow and velocity fields. The numerical simulation results showed that the new non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…As the full separation point is decayed by the nonsmooth surface, the region of adverse pressure will be reduced. This is different from the mechanism of drag reduction when flow passes a plain surface with grooves, as the low-speed roller-bearing-like swirl is formed within the non-smooth unit, which translates sliding friction between the object surface and fluid into rolling friction, leading to skin friction reductions (Song, Lin, Liu, & Zhou, 2017;Song, Zhang, & Lin, 2017).…”
Section: Achievementsmentioning
confidence: 94%
“…As the full separation point is decayed by the nonsmooth surface, the region of adverse pressure will be reduced. This is different from the mechanism of drag reduction when flow passes a plain surface with grooves, as the low-speed roller-bearing-like swirl is formed within the non-smooth unit, which translates sliding friction between the object surface and fluid into rolling friction, leading to skin friction reductions (Song, Lin, Liu, & Zhou, 2017;Song, Zhang, & Lin, 2017).…”
Section: Achievementsmentioning
confidence: 94%
“…, where y is the normal distance between the fluid and the wall and  is the thickness of the boundary layer [41]. By disturbing the near-wall turbulent region with a nonsmooth unit cell, a new turbulent boundary layer will be generated.…”
Section: Model Of a Bionic Nonsmooth Surfacementioning
confidence: 99%
“…The total length was set to 1.5 m, and the length of the test section was set to 0.3 m. To form a fully developed turbulent boundary layer at the inlet of the test section, a smooth section with a length of 1 m was arranged upstream. The normal distance from the far field boundary to the wall was 0.2 m. Preliminary research has found that turbulent drag is most influenced by the near-wall turbulent region of the boundary layer, defined as y/δ ≤ 0.2, where y is the normal distance between the fluid and the wall and δ is the thickness of the boundary layer [41]. By disturbing the near-wall turbulent region with a nonsmooth unit cell, a new turbulent boundary layer will be generated.…”
Section: Computational Domain Selection and Grid Divisionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the initial stage of the occurrence of vortex, the variation of scale’s angle could prevent the vortex from further development and finally suppress the occurrence of vortex 12 14 . Inspired by shapes of barchan dunes in deserts, Song et al found trough numerical simulation that the maximum drag reduction rate of bionic non-smooth surface was 33.63% 15 . Kumagai et al studied the drag reduction effect of micro-bubbles by injecting airflow into the machinery’s surface to form a layer of micro-bubbles.…”
Section: Introductionmentioning
confidence: 99%